"Effectivity" in International Law: Self-Empowerment against Epistemological Claustrophobia. (2014) - d'Aspremont, Jean
Abstract : When we think of "effectivity, " we usually come to think of a pragmatic and factual construction. The idea of effectivity, however, is anything but concrete and raises a variety of questions of legal theory, legal philosophy, epistemology, and theory of knowledge. It should also be highlighted that from a linguistic standpoint the word effectivity does not exist in British English. The attachment of the International Court of Justice to her Majesty's English explains that the World Court uses the French word ( effectivité ) when it seeks to refer to effectivity. These linguistic debates, however, matter less than the semantics and especially less than the consensus that effectivity ought to be opposed to "effectiveness."